2015
DOI: 10.1038/srep09759
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proximal ectodomain cleavage of MUC16 occurs in the acidifyingGolgi/post-Golgi compartments

Abstract: MUC16, precursor of the most widely used ovarian cancer biomarker CA125, is up regulated in multiple malignancies and is associated with poor prognosis. While the pro-tumorigenic and metastatic roles of MUC16 are ascribed to the cell-associated carboxyl-terminal MUC16 (MUC16-Cter), the exact biochemical nature of MUC16 cleavage generating MUC16-Cter has remained unknown. Using different lengths of dual-epitope (N-terminal FLAG- and C-terminal HA-Tag) tagged C-terminal MUC16 fragments, we demonstrate that MUC16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 46 publications
4
49
0
Order By: Relevance
“…MUC13 contains a SEA domain without a conserved cleavage motif, but gel analysis showed that the mature protein does consist of 2 polypeptides [25]. Cleavage of MUC16 does not occur in a conserved sequence in 1 of the SEA domains, but occurs close to the transmembrane domain [26]. This cleavage occurs in an acidic compartment of the Golgi complex and is independent of the amino acid sequence as mutation still resulted in cleavage.…”
Section: General Features Of Transmembrane Mucinsmentioning
confidence: 99%
See 2 more Smart Citations
“…MUC13 contains a SEA domain without a conserved cleavage motif, but gel analysis showed that the mature protein does consist of 2 polypeptides [25]. Cleavage of MUC16 does not occur in a conserved sequence in 1 of the SEA domains, but occurs close to the transmembrane domain [26]. This cleavage occurs in an acidic compartment of the Golgi complex and is independent of the amino acid sequence as mutation still resulted in cleavage.…”
Section: General Features Of Transmembrane Mucinsmentioning
confidence: 99%
“…MUC13 expression leads to transcriptional modulation of the genes involved in apoptosis and cell proliferation (see below), but it is unclear if this effect is a result of signaling activity or directly caused by nuclear localization [88]. Cleavage of MUC16 results in a C-terminal fragment containing the transmembrane domain and an intracellular tail that can traffic to the nucleus and bind chromatin [26]. Through interaction with JAK2, this MUC16 fragment upregulates the expression of stem cell genes LMO2 and NANOG in pancreatic cancer cells [148].…”
Section: Contribution Of Mucins To Carcinogenesis and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent the lack of antibodies for the C-terminal MUC16, we used dual epitope tagging of various lengths of carboxyl-terminal MUC16 fragments to narrow down the potential site of cleavage. We observed that earlier predicted sites #1 and #2 are not essential for MUC16 cleavage, instead a novel stretch of 12 amino acids in the juxta-membrane ectodomain (PLTGNSDLPFWA) was found to be sufficient for MUC16 cleavage (11) ( Figure 1A ). While this novel stretch of 12 amino acids was found to be sufficient for MUC16 cleavage, it is not an absolute necessity, as deletion of this stretch did not result in complete abrogation of MUC16 cleavage (11).…”
Section: Introductionmentioning
confidence: 64%
“…Although the potential of using CA125 towards (i) monitoring the response to OC treatment, (ii) recurrence of the disease (OC) following treatment and/or (iii) early detection of the disease was soon realized, its molecular characterization took an overwhelmingly long two decades time till 2001, when Lloyd and O'Brien's groups independently demonstrated that CA125 is indeed a very large membrane bound mucin MUC16 (1-3). Since then, several groups including ours have attempted to characterize MUC16 with respect to its cleavage (11), trafficking (12), regulation of expression (13, 14) and its functional involvement in health and disease (15-21). Recently, Cheon D-J et al , generated and characterized a whole body Muc16 knock out mouse model (22).…”
Section: Introductionmentioning
confidence: 99%